The relationship of oral malodor in patients with or without periodontal disease - Figueiredo, L. C.; Rosetti, E. P.; Marcantonio, E.; Marcantonio, Rosemary Adriana Chierici [UNESP]; Salvador, S. L. (Amer Acad Periodontology, 2002)
Background: Halitosis has been correlated with the concentration of volatile sulfur compounds (VSC) produced in the oral cavity by metabolic activity of bacteria colonizing the periodontal area and the dorsum of the tongue. The aim of this study was to determine whether there is some relationship between the presence of N-benzoyl-DL-arginine-2-napthylamide (BANA)positive species Treponema denticola, Porphyromonas gingivalis, and Bacteroides forsythus and clinical and oral malodor parameters.Methods: Twenty-one subjects (21 to 59 years old) with probing depths (PD) >3.0 mm and 20 subjects (21 to 63 years old) with PD less than or equal to3.0 mm (controls) participated. The quality of the mouth air was assessed organoleptically, and a portable sulfide monitor was used to measure the concentration of VSC. Clinical parameters, plaque index (PI) and gingival index (GI), were obtained from 6 teeth. Samples for BANA test were taken from the dorsal surface of the tongue, saliva, and the 6 reference teeth.Results: the scores of PI, GI, subgingival samples that tested positive for BANA hydrolyzing species, organoleptic ratings, and VSC values were significantly higher in the subjects with PD >3.0 mm (P <0.01, Mann-Whitney U test). There was a correlation between BANA hydrolysis by subgingival plaque bacteria and VSC values (r = 0.55, P <0.01), and between GI and VSC values (r = 0.48, P <0.05) in patients with PD >3.0 mm. There was no significant correlation between these parameters in the control group.Conclusion: These results confirm that the BANA hydrolyzing bacteria in the subgingival plaque are an important source of malodor production in the oral cavity.
Keywords: halitosis/etiology; BANA test; dental plaque/microbiology; periodontal diseases/microbiology; sulfur compounds